Pappa2 deletion in mice affects male but not female fertility. Issue 1 (December 2015) - Christians, Julian; King, Avery; Rogowska, Monika; Hessels, Sonia
Abstract Background Recent studies have found associations between the gene encoding pregnancy associated plasma protein-A2 (PAPP-A2), a protease of insulin-like growth factor binding protein -5 (IGFBP-5), and measures of female reproductive performance in cattle. The purpose of the present study was to test the effects ofPappa2 deletion on reproduction in mice. Findings We measured the fertility and offspring growth ofPappa2 deletion females, and also performed reciprocal matings (i.e., deletion males mated to control females) to control for the effects of offspring genotype. Ovarian and testicular IGFBP-5 levels were measured by Western blotting. As expected, deletion ofPappa2 increased ovarian IGFBP-5 levels. However, Pappa2 deletion in females had no effect on the interval between pairing and the birth of the first litter, the interval between the births of the first and second litters, or litter size. Offspring weight was lower in the offspring ofPappa2 deletion females, but effects of similar magnitude were observed in the offspring ofPappa2 deletion males, suggesting that the effects were due to heterozygosity for the deletion in the offspring.Pappa2 deletion in males had no effect on litter size or the interval between pairing and the birth of the first litter. However, the interval between the births of the first and second litters was significantly longer in deletion males. Conclusions Pappa2 deletion had no effect on female reproductive performance. In contrast, Pappa2 deletion had subtle effects on male fertility, although the underlying mechanism remains to be elucidated.